2019
DOI: 10.1101/657932
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microstructural plasticity in the bilingual brain

Abstract: The human brain has been uniquely equipped with the remarkable ability to acquire more than one language, as in bilingual individuals. Previous neuroimaging studies have indicated that learning a second language (L2) induced neuroplasticity at the macrostructural level. In this study, using the quantitative MRI (qMRI) combined with functional MRI (fMRI) techniques, we quantified the microstructural properties and tested whether second language learning modulates the microstructure in the bilingual brain. We fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Earlier studies following the tradition of Critical Period Hypothesis tended to highlight AoA as a key variable for brain activity patterns (Kim et al, 1997;Weber-Fox & Neville, 2007), but later studies with fMRI/PET found that proficiency was more important (e.g., see Abutalebi et al, 2005 for review). However, various studies continued to point out the important role of AoA (e.g., Klein et al, 2014;Luo et al, 2019), and researchers have also been interested in disentangling the independent contributions of AoA and L2 proficiency (e.g., Nichols & Joanisse, 2016; see also Hernandez & Li, 2007). More recent work also has shown that bilinguals vary considerably in terms of cortical structure depending on AoA.…”
mentioning
confidence: 99%
“…Earlier studies following the tradition of Critical Period Hypothesis tended to highlight AoA as a key variable for brain activity patterns (Kim et al, 1997;Weber-Fox & Neville, 2007), but later studies with fMRI/PET found that proficiency was more important (e.g., see Abutalebi et al, 2005 for review). However, various studies continued to point out the important role of AoA (e.g., Klein et al, 2014;Luo et al, 2019), and researchers have also been interested in disentangling the independent contributions of AoA and L2 proficiency (e.g., Nichols & Joanisse, 2016; see also Hernandez & Li, 2007). More recent work also has shown that bilinguals vary considerably in terms of cortical structure depending on AoA.…”
mentioning
confidence: 99%